Modulatory Effects of Date Palm (Phoenix dactylifera L.) Pits Extract Against Ethinylestradiol Induced Genotoxic Damage in Cultured Human Lymphocytes - Al-Juraisy, Yasir H. (Iraqi Journal of Science, 2022)
Ethinylestradiol is widely used in oral contraceptive formulations and also for the treatment of various sexual and metabolic disorders. It is not only a genotoxic agent but also a tumor initiating agent. In the present study, the modulatory effect of aqueous extract of date pits was evaluated against the genotoxic effect induced by ethinylestradiol on human lymphocytes using chromosomal aberrations (CA), blast index (BI), mitotic index (MI), sister chromatid exchanges (SCE) and replication index (RI) as parameters. The date pits extract was evaluated at 1.075x10-4, 2.125x10-4, 3.15x10-4 and 4.17x10-4 g/ml along with 10 μM of ethinylestradiol in culture medium. The results showed a significant dose-dependent decrease in the frequency of CA and SCE induced by ethinylestradiol. The results of the present study suggest that the plant extract per se does not have genotoxic potential, but can modulate the genotoxicity of ethinylestradiol in cultured human lymphocytes.